Grundtvig på normaldansk - Michelsen, William (Grundtvig-studier, 1989)
Grundtvig in Normal Danish.Helge Grell: The Spirit of the Creator and the Spirit of the People. An examination of Grundtvig’s ideas about peoples and popular culture, and their connection with his Christian view. Anis Publishing House, Århus. 346 pp.A Human First, A Christian Next. Helge Grell’s dissertation on Grundtvig under debate. Edited by Jens Holger Schjørring, the writers, and Anis Publishing House. Århus, 1988. 101 pp.Grundtvig’s prose is difficult to read, even for Danes. In this book Helge Grell has made his ideas about people, nations, and popular culture readable and intelligible. He has also examined Grundtvig’s relations with the non-Danish writers who have dealt with nationality and nationalism, and whom Grundtvig has known. The main problem has been whether Grundtvig - particularly in his writings from 1810 to 1865 - misused Christianity for the purpose of nationalistic propaganda against Germany, which he has been accused of, especially as regards the time around the two Schleswig wars, 1848-50 and 1864.The book is a chronological study of Grundtvig’s ideas from 1810 to 1865 which shows that his thoughts about peoples and popular culture have grown out of the particular philosophy and theology of creation that Grundtvig developed after his Christian revival in 1810 and which found its practical theological form especially in his years as pastor from 1821, and during his three journeys to England 1829-1831. From 1821 Grundtvig sees God’s work of creation as an act of love, which in the course of history has led Him to include the creation of peoples and popular culture. Grundtvig now sees the Holy Ghost as the spirit of human history who creates an interaction between God’s word and man’s word in its national form: the mother tongue, and who works through the spirit of a people. His ideas about people and popular culture are thus brought into connection with the Mosaic-Christian view of human life as a whole.To Grundtvig the Jewish people with its particular history constitutes what he understands by an "artificial people” in which the national spirit has, ’’with marvellous artistry”, created a unique God-chosen people from whose history Christianity was to develop (Selected Works, vol.V, p. 401-425). Grundtvig substitutes the phrase for Fichte’s "normal people”. Grell writes in this connection: ” The view of man of this people, developed through Christianity, must stand as normative in the interaction with the spirits of the two other great peoples, i.e., those of Greece and the Nordic countries, in order that they may serve universal history, and all other peoples are evaluated (by Grundtvig) in comparison with them." Grundtvig uses the term "natural peoples” for these two other principal peoples, i.e., peoples whose history can be traced chronologically, and who have preserved a living connection with the people’s spirit through a living mother tongue.A people’s spirit is regarded by Grundtvig as an image of God’s creator- spirit, just as poetry with its imagery is. Grell has made a more elaborate examination of Grundtvig’s theology of the Word in his preliminary study for the dissertation "The Creator Word and the Figurative Word”, which was published in 1980 and was reviewed in Grundtvig Studies 1982. It is also included in the German summary appended to the dissertation. It is through this close connection between Grundtvig’s theology of the Creation and his theology of the Word that Grell succeeds in defending Grundtvig against the accusations of nationalistic propaganda. Grell rightly claims that it is this key theme in his writings that must be attacked if one wants to make any effective criticism of his ideas about peoples and popular culture.Grell’s two theses are not directed against any other view of Grundtvig’s thinking. Only in the conclusion of the work did it appear that his dissertation might be read as an alternative to Kaj Thanings understanding of Grundtvig ("A Human Being First...”, Dissertation, Copenhagen 1963). A good deal of the debate during and after the public defence has therefore turned on this question, which in the dissertation is only brought up in the comprehensive notes. The dialogue between Thaning and Grell clearly demonstrates the mutual respect of the two scholars, but causes neither of them to change their attitudes or standpoint.